Blood omega-3 fatty acids and death from COVID-19: A pilot study. (March 2021) - Asher, Arash; Tintle, Nathan L.; Myers, Michael; Lockshon, Laura; Bacareza, Heribert; Harris, William S.
Highlights: Nutrition-based interventions to reduce COVID-19 morbidity/mortality are needed. The Omega-3 Index (O3I) was measured in banked blood from 100 COVID-19 patients. Risk for death was analyzed as a function of quartiles (Q) of the O3I. Patients in Q4 (O3I ≥ 5.7%) vs. Q1–3 were 75% less likely to die ( p  = 0.07). These pilot data suggest that a higher O3I may lower risk for death from COVID-19. Abstract: Very-long chain omega-3 fatty acids (EPA and DHA) have anti-inflammatory properties that may help reduce morbidity and mortality from COVID-19 infection. We conducted a pilot study in 100 patients to test the hypothesis that RBC EPA+DHA levels (the Omega-3 Index, O3I) would be inversely associated with risk for death by analyzing the O3I in banked blood samples drawn at hospital admission. Fourteen patients died, one of 25 in quartile 4 (Q4) (O3I ≥5.7%) and 13 of 75 in Q1–3. After adjusting for age and sex, the odds ratio for death in patients with an O3I in Q4 vs Q1–3 was 0.25, p  = 0.07. Although not meeting the classical criteria for statistical significance, this strong trend suggests that a relationship may indeed exist, but more well-powered studies are clearly needed.